Wavelet Transform for Real-Time Detection of Action Potentials in Neural Signals - Quotb, Adam; Bornat, Yannick; Renaud, Sylvie (Frontiers in Neuroengineering, 2011)
We present a study on wavelet detection methods of neuronal Action Potentials (APs). Our final goal is to implement the selected algorithms on custom integrated electronics for on-line processing of neural signals; therefore we take real-time computing as a hard specification and silicon area as a price to pay. Using simulated neural signals including APs, we characterize an efficient wavelet method for action potential extraction by evaluating its detection rate and its implementation cost. We compare software implementation for three methods: adaptive threshold, Discrete Wavelet Transform (DWT) and Stationary Wavelet Transform (SWT). We evaluate detection rate and implementation cost for detection functions dynamically comparing a signal with an adaptive threshold proportional to its standard deviation, where the signal is the raw neural signal, respectively: i) non processed; ii) processed by a Discrete Wavelet Transform (DWT); iii) processed by a Stationary Wavelet Transform (SWT). We also use different mother wavelets and test different data formats to set an optimal compromise between accuracy and silicon cost. Detection accuracy is evaluated together with false negative and false positive detections. Simulation results show that for on-line AP detection implemented on a configurable digital integrated circuit, APs underneath the noise level can be detected using SWT with a well-selected mother wavelet, combined to an adaptive threshold.